Management of Production and Services Units in Improving Students' Skills and the Absorption of Graduates: An Analysis on Welding Expertise Competency - Ardhianzah, Rizal; Widiyanti, Widiyanti; Yoto, Yoto (Belantika Pendidikan, 2022)
Research on the management of UPJ in Welding Engineering Skills Competence at SMK Sore Tulungagung and SMKN 2 Tulungagung in an effort to improve student skills and absorption of graduate students is a descriptive research method with a qualitative approach. The results showed that the POAC management model was the UPJ management model used in SMK Sore Tulungagung and SMKN 2 Tulungagung. UPJ management activities according to the POAC model consist of four activities which include planning, organizing, implementing, and supervising.